The role of skin bank in the treatment of severely burnt patients - Dvoránková, B; Broz, L; Pafcuga, I; Kapounková, Z; Königová, R (Acta chirurgiae plasticae, 2004)
The accessibility of suitable temporary covers plays the key role in the treatment of severe skin losses. Biological covers have got the longest tradition in the wound healing. Skin banks are engaged in their production and distribution. Already in 1973 J. Moserová developed the methodology of harvesting pig xenografts. Later on, the short-term and the long-term method of storage were verified (Böhm, Konícková, Vogtová). In 1986, the Skin Bank in the Prague Burn Centre was established. In Prague Burn Centre the allografts are used very rarely, usually from the living donors, family members of the patients. Therefore, in our bank, we specialized in harvesting porcine xenografts. They are produced in three different forms--fresh, deep frozen in vapours of liquid nitrogen, and glycerolized. Porcine xenografts serve as a biological cover; they make barrier against infection and evaporation and protect the wound against desiccation. They are used namely for the treatment of superficial burn wounds, as a temporary coverage of excised wounds and as a dressing on release incision. Every year more than 10,000 strips have been used in our Burn Centre, it represents the area 200 m2. Since 1991 cultivation laboratory has been a part of our Skin Bank. We are interested in cultivation of human epidermal cells--keratinocytes. Cultured epidermal grafts became the first human in vitro prepared tissue, which was successfully transplanted to the patient. For the treatment of deep dermal skin losses we use either autologous keratinocytes, which can create permanent cover, or allogeneic cells, which stimulate spontaneous healing. Cultured keratinocytes are used in the treatment of burnt patients as well as in the trophic defects.
Keywords: biologické krytí; popálení; Animals; Biological Dressings; tkáňové banky; Burns; lidé; Czech Republic; Swine; Skin Transplantation; transplantace kůže; Humans; prasata; Keratinocytes; keratinocyty; Česká republika; Tissue Banks; zvířata